Implementasi Habituasi Pembelajaran Salaf dan Khalaf dalam Pendidikan Karakter Siswa MA Denanyar Jombang - Mega Putri Wulandari; Chusnul Chotimah; Muhammad Fodhil (Lembaga Yasin AlSys, 2026)
Although character education has become a major concern in Islamic education, studies that specifically discuss the integration of salaf and khalaf learning habituation as a comprehensive approach to shaping students’ character remain limited. This study aims to analyze the implementation of salaf and khalaf learning habituation and its role as an alternative model in shaping students’ character at MA Mu’allimin Mu’allimat Mamba’ul Ma’arif Denanyar Jombang. This study used a qualitative approach with a case study design, involving the head of the madrasah, teachers, and students selected through purposive sampling. Data were collected through passive participant observation, in-depth interviews, and documentation, then analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. Data validity was tested through source and technique triangulation. The results showed that the integration of salaf learning through the study of kitab kuning, religious habituation, and the internalization of adab, as well as khalaf learning through the formal curriculum with active methods, was implemented continuously in classroom learning activities and the culture of daily life in the madrasah. This approach was effective in developing students’ religious character, discipline, responsibility, tolerance, and balance between intellectual and moral intelligence. These findings emphasize the importance of integrating traditional Islamic values with modern educational approaches as an alternative model for strengthening sustainable character education in Islamic educational institutions.